E-Commerce Shopee Marketing Strategy in International Business - Mela Devita; Zuhrinal M Nawawi Nawawi; Nuri Aslami (International Journal Labs, 2022)
Background: The lifestyle of modern society and economy has been shaped by the advancement and evolution of information technology. Shopee implements worldwide marketing strategies to achieve success in foreign business. Objective: The purpose of this research is to find out how Shopee's marketing approach has developed and grown in foreign markets. Methods: This study uses a descriptive approach and uses a qualitative strategy. This research is based on secondary data collection. Results: generate marketing benefits and increased trade as it attracts many new customers, enables Shopee to conduct international trade exchanges and serves as a link between the domestic and global economies. Conslusion: The advancement of life combined with the availability of information and communication technology, as well as the use of the internet, has resulted in the creation of a multinational business. Consumers play an important role in shaping all commercial and manufacturing operations in the modern economy, so businesses that emerge in this era must be able to match their desires.